A Clinical Trial of the Effects of a Dietary Pattern on Health Metrics and Fecal Metabolites in Volunteers With Risk of Cardiovascular Disease - Han, Kunchen; Ma, Jinke; Dou, Junxia; Hao, Dan; Zhu, Wenjun; Yu, Xiaohan; Zheng, Wenxuan; Song, Yao; Shi, Fengcui; Li, Quanyang (Frontiers in Nutrition, 2022)
The phenomenon of longevity in Guangxi of China proved to be closely relevant to its specific dietary habits, but the exact effects of this diet on health remain to be explored. In this work, fourteen screened volunteers with cardiovascular disease (CVD) risk followed a novel dietary pattern derived from centenarians of Guangxi, China for two weeks, then the effects of diet on human health were explored by measuring the health metrics and fecal metabolites. The results showed that the short-term dietary intervention significantly decreased the body weight, body mass index (BMI), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-c), mean systolic blood pressure (SBP), and diastolic blood pressure (DBP) levels, while it significantly increased high-density lipoprotein cholesterol (HDL-c) levels. Orthogonal partial least squares discriminant analysis (OPLS-DA) indicated a distinct separation in the fecal metabolic profiles of volunteers before and after the intervention. Nine of these metabolites showed significant differences, including two metabolites increased (butyrate, citrulline), seven metabolites decreased (threonine, choline, glycine, aspartate, alanine, N-acetylglutamic acid, lysine). Pathway and enrichment analysis showed that the reduction in CVD risk by dietary intervention mainly affected five pathways, which include arginine biosynthesis; aminoacyl tRNA biosynthesis; glycine, serine and threonine metabolism; alanine, aspartate and glutamate metabolism; and valine, leucine and isoleucine biosynthesis. Herein, the Guangxi longevity dietary pattern can provide a feasible healthy diet strategy for reducing the CVD risk and human beings.